2021
DOI: 10.3390/ijerph18094602
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of IPAQ-SF and GPAQ for Assessing Sedentary Behaviour in Adults in the European Union: A Systematic Review and Meta-Analysis

Abstract: Current lifestyles are marked by sedentary behaviour; thus, it is of great importance for policymaking to have valid and reliable tools to measure sedentary behaviour in order to combat it. Therefore, the aim of this review and meta-analysis is to critically review, assess, and compile the reliability, criterion validity, and construct validity of the single-item sedentary behaviour questions within national language versions of most commonly used international physical activity questionnaires for adults in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 55 publications
2
46
1
1
Order By: Relevance
“…As expected, one of the most valid constructs in all selected PAQs was sedentary behavior. However, the associations in our study were low (0.38–0.45), while other studies found moderate to high correlations [ 30 ]. Nevertheless, the correlation coefficients for sedentary behavior in our study were still higher than in the two previous research that used the same device.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…As expected, one of the most valid constructs in all selected PAQs was sedentary behavior. However, the associations in our study were low (0.38–0.45), while other studies found moderate to high correlations [ 30 ]. Nevertheless, the correlation coefficients for sedentary behavior in our study were still higher than in the two previous research that used the same device.…”
Section: Discussioncontrasting
confidence: 97%
“…The test-retest reliability results of all three PAQs were adequate (low to high correlations); the alpha coefficient also showed good internal consistency of IPAQ-SF and GPAQ and moderate internal consistency of EHIS-PAQ. Concurrent validity was high and significant for the sedentary behavior items between all three PAQs; comparable results were obtained in a recent meta-analysis for IPAQ-SF and GPAQ [ 30 ]. Compared to the UKK RM42 accelerometer physical activity data, PAQs showed lower performance.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…PA was assessed by the Chinese version of the International Physical Activity Questionnaire-Short Form (IPAQ-SF), which has adequate validity and reliability (Mengyu, Fan et al, 2014 ; Meh et al, 2021 ). The participants reported days and times of PA during the last 7 days.…”
Section: Methodsmentioning
confidence: 99%